Processing architecture. (June 2016) - Leitão, António; Caetano, Inês; Correia, Hugo
Programming promotes creative freedom but might require considerable effort to learn. The Processing language was created to simplify this learning process. Due to its graphical capabilities, the language has become very popular among the electronic arts and design communities. Unfortunately, this popularity could not be extended to the architecture community, which relies on traditional heavyweight computer-aided design and building information modeling applications that cannot be programmed using Processing. As a result, it becomes difficult for architects to take advantage of Processing. To solve this problem, we propose an implementation of Processing that runs in the context of the most used computer-aided design tools in architecture. Our implementation allows Processing to generate two- or three-dimensional models that are directly usable for architectural work. To this end, we also propose extensions to the language, including three-dimensional modeling primitives that dramatically simplify the effort needed for developing large and complex architectural models with Processing.